Centella Asiatica Leaf Extract Increases FGF2 and Improves Paw Histopathology in Acute-Inflammation Rats - Ratna Mega Sary; Endy Juli Anto; Jekson Martiar Siahaan (Indonesian Journal of Global Health Research, 2026)
Excessive acute inflammation causes oedema and tissue injury, while conventional anti-inflammatory drugs are limited by adverse effects. Centella asiatica contains bioactive compounds with anti-inflammatory and pro-healing properties; VEGF and FGF2 mediate angiogenesis and tissue repair. To evaluate the effect of C. asiatica leaf ethanol extract on serum VEGF and FGF2 levels and paw histopathology in rats with acute inflammation. Thirty male Wistar rats were randomised into five groups: normal, negative control (carrageenan), positive control (sodium diclofenac), and extract 2 and 4 g/kgBW orally. Acute inflammation was induced by subplantar carrageenan; paw volume, serum VEGF and FGF2 (ELISA), and haematoxylin-eosin histopathology were assessed. Data were analysed by ANOVA and post hoc LSD. FGF2 differed significantly among groups (p<0.001); carrageenan lowered FGF2 whereas the extract increased it (2 g/kgBW 410.76; 4 g/kgBW 335.42 pg/mL). VEGF was unchanged (p=0.713). The 4 g/kgBW dose reduced oedema and neutrophil infiltration comparably to the positive control. C. asiatica leaf ethanol extracts increased FGF2 and improved acute-inflammation histopathology, particularly at 4 g/kgBW.